2014
DOI: 10.1016/j.molonc.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 inhibition enhances cisplatin‐mediated alterations in tumor cell proliferation, metabolism, and metastasis

Abstract: Tumor cells have unstable genomes relative to non-tumor cells. Decreased DNA integrity resulting from tumor cell instability is important in generating favorable therapeutic indices, and intact DNA repair mediates resistance to therapy. Targeting DNA repair to promote the action of anti-cancer agents is therefore an attractive therapeutic strategy. BRCA2 is involved in homologous recombination repair. BRCA2 defects increase cancer risk but, paradoxically, cancer patients with BRCA2 mutations have better surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Recently, increasing studies have shown that activation of Aur A or inactivation/mutation of BRCA2 is associated with cancer metastasis [2933]. In spite that different signal pathways have been reported, the tumor suppressor p53 may still play an important role in terms of the Aur A and BRCA2 status during cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing studies have shown that activation of Aur A or inactivation/mutation of BRCA2 is associated with cancer metastasis [2933]. In spite that different signal pathways have been reported, the tumor suppressor p53 may still play an important role in terms of the Aur A and BRCA2 status during cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these types of resistance, a second drug must be added to offset the mentioned drug-resistance mechanisms to drive cell death. For example, addition of BRCA2 antisense oligonucleotide which inhibited the DNA repair significantly enhanced the cytotoxicity of ciplatin to cancer cells [7]. Given this, combined treatment with other drugs is desirable to decrease the dose of cisplatin and overcome the cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of possible ESE's on the cryptic splice site c.3550 and c.2398 should be further experimentally validated (Di Giacomo et al., ; Raponi et al., ). Knowledge on potentially activated splice sites in case of inactivation of the WT site, may be important to design adequate BRCA2 ASOs (antisense oligonucleotides), which have been proposed as a promising avenue to prevent resistance to PARP inhibitor therapy in several tumor types (Rytelewski et al., ) or as potential therapeutic anti‐cancer agent in combination with cisplatin (Rytelewski et al., ).…”
Section: Discussionmentioning
confidence: 99%